A Novel α/β Hydrolase Domain Protein Derived From Haemonchus contortus Acts at the Parasite-Host Interface - Lu, Mingmin; Tian, Xiaowei; Tian, Ai-Ling; Li, Charles; Yan, Ruofeng; Xu, Lixin; Song, Xiaokai; Li, Xiangrui (Frontiers in Immunology, 2020)
The α/β-hydrolase domain (ABHD) proteins belonging to α/β-hydrolase (ABH) superfamily are ubiquitously distributed throughout all the organisms, and their functional roles have been implicated in energy metabolism, cell signalling, growth and development. In our preliminary work, we identified a novel ABHD protein derived from Haemonchus contortus excretory-secretory (ES) proteins (HcESPs) that interacted with host T cells. Here, we demonstrated that H. contortus ABHD (HcABHD) protein, expressed in all life-cycle stages of H. contortus, is a mammalian ABHD17 homologue with immunodiagnostic utility and lipase activity. Given its catalytic activities and immunomodulatory potentials, we further investigated the functional diversity of HcABHD as an individual ES protein in parasite-host interactions. HcABHD protein may serve as depalmitoylase or thioesterase to suppress cell viability, inhibit cell proliferation, induce intrinsic and extrinsic T cell apoptosis, and cause cell cycle arrested at G1 phase. Moreover, recombinant HcABHD stimuli exerted critical controls on T cell cytokine production profiles, predominantly by inhibiting the secretions of interleukin (IL)-4, interferon-gamma (IFN-γ) and transforming growth factor-beta (TGF-β) 1, and promoting IL-10 production. As the immunomodulator acting at the parasite-host interface, HcABHD protein may have potential applications for the vaccine development of therapeutic intervention. Together, these findings may help illuminate the molecular and particularly immunomodulatory aspects of ES proteins and contribute to an enhanced understanding of parasite immune evasion in H. contortus-host biology.